Genetic Variants in Patients with Multiple Head and Neck Paragangliomas: Dilemma in Management - Guha, Anasuya; Vicha, Ales; Zelinka, Tomas; Musil, Zdenek; Chovanec, Martin (Biomedicines, 2021)
Multiple head and neck paragangliomas (HNPGLs) are neuroendocrine tumors of a mostly benign nature that can be associated with a syndrome, precipitated by the presence of a germline mutation. Familial forms of the disease are usually seen with mutations of SDHx genes, especially the SDHD gene. SDHB mutations are predisposed to malignant tumors. We found 6 patients with multiple tumors amongst 30 patients with HNPGLs during the period of 2016 to 2021. We discuss the phenotypic and genetic patterns in our patients with multiple HNPGLs and explore the management possibilities related to the disease. Fifty percent of our patients had incidental findings of HNPGLs. Twenty-one biochemically silent tumors were found. Four patients had germline mutations, and only one had a positive family history. Three out of five underwent surgery without permanent complications. Preventative measures (genetic counselling and tumor surveillance) represent the gold standard in effectively controlling the disease in index patients and their relatives. In terms of treatment, apart from surgical and radiotherapeutic interventions, new therapeutic measures such as gene targeted therapy have contributed very sparsely. With the lack of standardized protocols, management of patients with multiple HNPGLs still remains very challenging, especially in those with sporadic or malignant forms of the disease.